1976
DOI: 10.1139/v76-484
|View full text |Cite
|
Sign up to set email alerts
|

The thermally induced rearrangements of 2-vinyloxirane

Abstract: . Can. J. Chem. 54, 3364 (1976).The kinetics of the gas phase thermoiysis of Zvinyloxirane (4) have been studied over the temperature range 270-310 "C. The racemization of chiral 4 occurs six times faster than the structural ison~erization to 2,3-dihydrofiran, (E)-and (d)-2-butenai, and 3-butenal. The butenals undergo a slow ihermolysis to propene and carbon monoxide. cis-Deuterio-and frnr2s-3-deuterio-vhyioxirai1~ have been synthesized and their interconversion is slow. Deuterium kinetic isotope ezects on mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 6 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…It is known that vinyloxirane undergoes rapid ring expansion to 2,3-dihydrofuran at relatively low temperatures [13,14] [15] to be unimolecular isomerizations to crotonaldehyde and cyclopropanecarboxaldeldehyde.…”
Section: 3-butadiene Oxidationmentioning
confidence: 99%
“…It is known that vinyloxirane undergoes rapid ring expansion to 2,3-dihydrofuran at relatively low temperatures [13,14] [15] to be unimolecular isomerizations to crotonaldehyde and cyclopropanecarboxaldeldehyde.…”
Section: 3-butadiene Oxidationmentioning
confidence: 99%
“…We suggested that the decarbonylation of 3-butenal was both radical catalyzed and under oxygen free conditions proceeding via an intramolecular mechanism. To study this more thoroughly we have examined the thermolysis of the non-enolizable 2,2-dimethyl-3-butenal (1). There are few instances of decarbonylation of P,y-unsaturated aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…1 Although less relevant to our task, it was also known that vinyl oxiranes can be thermally ring expanded at high temperatures (>350°C) to form oxonium ylide intermediates, which then cyclize to form 2,3-dihydrofuran products. 2 Researchers had shown that catalysts could selectively insert into the allylic C-O vinyl oxirane bond and that the intermediate metallocycle could be used for ring expansions, which, in the examples shown, were used to form β-lactones. 3 The few ring expansion 'solutions' that were reported were low yielding, used substrates that were rigged to avoid the detrimental hydride shift pathway, or relied on an S N 2' type strategy using, in most cases, iodide as a nucleophile.…”
mentioning
confidence: 99%
“…6 We deliberately chose a vinyl oxirane substrate to study that was quite sensitive to Lewis acids and, as a result, formation of the unwanted aldehyde side product. Our first successful copper(II) catalyst that significantly favored 2,5-dihydrofuran formation was copper(II)acetylacetonate [Cu(acac) 2 ]. Despite the relatively high temperatures (150°C) and long reaction times (17 h), we were excited about this result.…”
mentioning
confidence: 99%
See 1 more Smart Citation